Madrasah Aliyah Swasta Tarbiyah Islamiyah Batang Kabung Kecamatan Koto Tangah Kota Padang 1988-2022 - Suci Sudirman; Abdul Salam (Jurnal Kronologi, 2023)
This study discusses the private Madrasah Aliyah Tarbiyah Islamiyah Batang Kabung, Koto Tangah District, Padang City in 1988-2022. The purpose of this study is to find out the background of the establishment and the dynamics of the development of MAS TI Batang Kabung in the Leadership period in 1988-2022. This study uses historical research methods which consist of four stages, namely Heuritic, Verification consisting of two (internal criticism and external criticism), Interpretation, and Histotiography. The results of this study indicate that the background to the establishment of MAS TI Batang Kabung was the desire of Sheikh Imam Maulana and the management of MTI Batang Kabung to develop the existing education system at MTI Batang Kabung for the Aliyah level which previously had an educational system at the Tsanawiyah level. MAS TI Batang Kabung is a continuation of MTs TI Batang Kabung. MAS TI Batang Kabung has been established since 1988 and was inaugurated in 1991. MAS TI Batang Kabung has experienced dynamic development per period of leadership where until 2022 there have been four leadership changes. The first period is the leadership of Prof. Dr. H. Duski Samad (1988-1993), the second is the leadership period of Bucimar Sani, BA (1994-2009), the third is the leadership period of Jamaris Amir, Tk Sutan (2009-2014), the fourth is the leadership period of Harun Bakhri, M.Pd (2014 - Now). The dynamics of these developments include the development of facilities and infrastructure, which was initially for only one class room until now there are 6 classes and the addition of other rooms such as computer laboratories, library rooms, science laboratory rooms, and other facilities and infrastructure. The development of santri, which was originally 15 people and in 2022 will reach 168 people. For curriculum development, MAS TI Batang Kabung previously used the Halaqah system and the Ministry of Religion curriculum for the State Examination and from 1994 to 2022, 3 types of curriculum have been used. Keywords: Development, Madrasah, Islamic Education Institutions